USING PODCASTS AS A TOOL TO ENHANCE EXTENSIVE LISTENING SKILLS - Erik Yuda Pratama; Winda Kurnia (ENGLISH, 2022)
The focus of the study is to explore the role of podcasts in enhancing students' extensive listening skills in learning English as a foreign language. The research involved eight students from the English Education Department of a private university in Indonesia, and data were collected through interviews, questionnaires, and guided reflective journals. The Case Study 2.0 framework was employed to collect and analyze data, which involved leveraging digital tools and platforms to enhance the traditional case study approach. The data collected were analyzed using qualitative data analysis techniques such as content and frequency analysis. The findings of the study findings revealed that podcasts were an effective tool for enhancing students' extensive listening skills, improving their pronunciation, vocabulary, and comprehension of English spoken by native speakers. The study also found that podcasts were engaging and motivating for students, leading to better learning outcomes. The study concludes that using podcasts is a beneficial approach to teaching listening skills in language learning.